PENGARUH SOAL BERBASIS HIGH ORDER THINKING SKILL (HOTS) TERHADAP HASIL BELAJAR BAHASA ARAB SISWA KELAS VIII MTS AL-KHAIRIYAH KELAPIAN BANTEN - Ihwan Mahmudi; Neni Naqiyah; Alif Cahya Setiyadi (At-Ta'dib, 2023)
The low Arabic language skills of students at MTs Al-Khairiyah Kelapian Banten are partly influenced by the use of questions that tend to measure Low Order Thinking Skills (LOTS). This research aims to determine the effect of using questions based on High Order Thinking Skills (HOTS) on the Arabic language learning outcomes of class VIII students at MTs Al-Khairiyah Kelapian Banten for the 2022 – 2023 academic year. This research uses a quantitative experimental method with a True Experimental Design research design with a Pretest-Posttest Control Group Design approach. The research sample consisted of 30 students who were divided into two classes, namely the experimental class and the control class. Research data was taken using tests. Data analysis uses the difference test. The results of the research show that there is an influence of HOTS-based questions on students' Arabic learning outcomes.